Rebuilding Hometowns: Religious Worship as an Identity and Tourist Strategies of Place-making - Carrera, Letizia; Calvo-Quirós, William (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
In a globalized world in which the paths of life project the subjects even in places distant from the birth one and in which the feeling of identity is pluralized and becomes more and more complex, new and stronger mechanisms of resistance and preservation of ties and sense of belonging are generated. The roots tourism represents an answer realized by the emigrants of first, second or even successive generations, able to preserve the link with the territory of origin and, through this, their own identity. This specific form of tourism is therefore, more than any other, a journey into its own history, characterized by the desire to (re)find places connected to its own past or family history. It seems that the identity sought a spatial, physical roots and, in experiencing those places, a sort of confirmation of the fullness of identity. In some cases, however, the return, even when periodic, to the country of origin or to which people feels to belong, is not felt as sufficient to bridge a distance experienced as a lack of identity. This complex dynamic sometimes takes the form of the choice to reproduce in the territory of arrival and in which subjects have consolidated their presence, especially religious traditions that reproduce, in form and manner, those of the city of origin. The aim, more or less consciously pursued, is to build and strengthen an individual and, at the same time, shared imaginary and an identity continuity that prescinds from the material distance that separates the places to which subjects feel to belong. A significant example is represented by the celebration of Mary SS. of Buterrito, also venerated as Madonna del Campo and whose feast falls on August 15, the day of the Assumption of Mary. This is an important celebration for the identity of the inhabitants of Ceglie del Campo, not only an historical place of the city of Bari but its original nucleus, is represented in an identical way also by the community of Ceglie emigrants who now lives in the city of Chicago in Illinois. The contribution aims to analyze these practices in their identity value. This first object will be flanked by a second one that will show, once again but in different forms, how much the re-proposal and especially the reproduction of religious rites is functional to build and maintain an identity bond with the place of origin. The proposed analysis will be enriched by a photographic apparatus that will not only make clearer the overlap and the coincidence of the forms of the religious ritual, but will be an integral part of the analysis itself.